Liquid crystal measurements of heat transfer and surface shear stress - Ireland, P; Jones, T (IOP, 2000)
Liquid crystals have become an accurate and convenient means of measuring surface temperature and heat transfer for the gas turbine and heat transfer research communities. The measurement of surface shear stress using liquid crystals is finding increasing favour with aerodynamicists and developments in these techniques ensure that liquid crystals will continue to provide key thermal and shear stress data in the future. The increasing use of three-dimensional finite element computational models has allowed industry to capitalize on the advantages of the full surface data generated. The paper reviews the use of these complex materials in research with a special emphasis on recent developments in the field. The aim is to provide the reader with an up to date background in this measurement technology and allow the researcher to decide whether liquid crystals would be suitable in specific applications.